A Simple Explanation of Stock Price Behavior in the Long Run: Evidence for Denmark - Jan Overgaard Olesen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
Using Danish data for the post-World War II-period, we estimate a simple model for the long-run behavior of stock prices. We find a stable and strong cointegrating relation between stock prices and two macroeconomic fundamentals variables, firm profits and the nominal bond rate. Both fundamentals are highly significant. Growth in profits drives the long-run trend in stock prices while the bond rate explains the observed large deviations from trend growth. The behavior of the bond rate accounts for the evident split of the Danish stock market into a bearish period before the early 1980s and a subsequent bullish period. Likewise, a decline in the bond rate explains a major part of the large capital gains realized in recent years.
Keywords: 330